PENGETAHUAN DAN DUKUNGAN ORANG TUA TERHADAP KEPATUHAN KONSUMSI TABLET TAMBAH DARAH PADA REMAJA PUTRI DI KECAMATAN PASAR MINGGU: PENGETAHUAN DAN DUKUNGAN ORANG TUA TERHADAP KEPATUHAN KONSUMSI TABLET TAMBAH DARAH PADA REMAJA PUTRI DI KECAMATAN PASAR MINGGU - Ery Kustini; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Iron does not only affect current health status but can also lead to complications that arise in the future. This study aims to determine the relationship between the level of knowledge of young women and their parents' support for compliance with iron supplement consumption. This study used a cross-sectional design. Sampling using simple random sampling with a total sample of 170 respondents. Data collection was carried out through questionnaires, field observations, and document studies. The results of the bivariate analysis with the chi-square test of knowledge with a value of p = 0.017 (p <0.05) which means that there is a significant relationship between the degree of knowledge and high blood pressure compliance. Based on parental support, the results obtained were p = 0.011 (p <0.05), which means that there was a significant relationship between parental support and adherence to taking iron tablets routinely. Compliance with iron supplement consumption is influenced by parental knowledge and support. In the future, it is necessary to conduct counseling for young women who lack knowledge by updating educational materials and looking for effective educational media to increase knowledge. Besides that, parental support at home to carry out periodic monitoring of young women's compliance in taking iron tablets, especially during holidays.